SIGN LANGUAGE IN THE SPORT AND PHYSICAL EDUCATION IN CROATIA (Fiep Bulletin - online, 2014)
The health effects of physical activity on the human body are often a subject of conversation, so there is no need to emphasize it. However, not all people have equal conditions, rights and opportunities to engage in physical activity. According to the data of the Croatian Association of the Deaf and Hard of Hearing, it is estimated that in the population of Croatia are 8000-10000 Deaf and 100000-150000 harder of hearing people. One of the main reasons, that the previous studies have suggested as a major cause of non-inclusion of deaf and hard of hearing people in organized forms of physical activity, is a communication barrier. Because of it, these people prefer to deal with such activities as walking, running or cycling. For equally involving deaf and hard of hearing people in all aspects of life, including the organized forms of physical activity, there is a need of learning sign language as part of the general culture. With this knowledge would be increase the number of people who can establish quality communication with deaf and hard of hearing people. Furthermore, future coachesand teachers of physical education with knowledge of sign language will be able, in a quality way, to transfer their sports knowledge onthis cultural minority. Hearing impaired people will open the door of sports activities in which so far they have not been able to participate because of the previously mentioned problems. That will also affected their better socialization, higher levels of self-esteem, self-confidence and quality of communication and interaction with other people.
Keywords: sign language; deaf; hard of hearing people; physical activity.